Do Firms Mitigate or Magnify Capital Misallocation? Evidence from Planet-Level Data - Matthias Kehrig; Nicolas Vincent (Center for Economic Studies and ifo Institute (CESifo), 2017)
Almost two thirds of the cross-plant dispersion in marginal revenue products of capital occurs across plants within the same firm rather than between firms. Even though firms allocate invest- ment very differently across their plants, they do not equalize marginal revenue products across their plants. We reconcile these findings in a model of multi-plant firms, physical adjustment costs and credit constraints. Credit constrained multi-plant firms can utilize internal capital markets by concentrating internal funds on investment projects in only a few of their plants in a given period and rotating funds to another set of plants in the future. The resulting increase in within-firm dispersion of marginal revenue products of capital is hence not a symptom of misallocation within the firm, but rather actions taken by the firm to mitigate external credit constraints and adjustment costs of capital. Economies with multi-plant firms produce more aggregate output despite higher dispersion in marginal revenue products of capital compared to economies with single-plant firms. Because emerging economies are predominantly populated by single-plant firms, the gains from reducing their distortions to the level of developed are larger than previously thought.
Keywords: E20; G30; 330; misallocation; productivity dispersion; multi-plants firms; internal capital markets